PENGARUH KOMPONEN KECERDASAN EMOSIONAL TERHADAP TINGKAT STRES KERJA AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK (KAP) DI PEKANBARU DAN MEDAN) - Delia -; Vince Ratnawati; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study to examine the influence of emotional intellegence, they are introduction of self, self-control,motivation, emphaty and social skills in auditor’s work stress.The samples in this study were auditors working at public accountants office (KAP) which registered in Pekanbaru and Medan. Methods of data collection in this study is the method of quesionnaire survey using instruments that are delivered directly to the public accountants office which registered in Pekanbaru and Medan. The respondents are used in the analysis were 55 respondents (42.3%). Methods of Analysis is conducted with a multiple regression a analysis using SPSS (Statistical Product and Service Solution) version 17.The results of this study, concluded introduction of self, self-control, motivation, social skills were have negative effect to auditor’s work stress. Whereas empathy was have positive effect to auditor’s work stress.Keywords: Auditor’s Work Stress, Introduction Self, Self-control, Motivation, Empathy, and Social skills.